2021
DOI: 10.1002/aur.2550
|View full text |Cite
|
Sign up to set email alerts
|

Early social rearing, the V1A arginine vasopressin receptor genotype, and autistic traits in chimpanzees

Abstract: Previous studies found associations between autism‐related phenotypes and both rearing and V1A arginine vasopressin receptor (AVPR1A) genotypes. We tested whether these exposures as well as their interaction were associated with autism‐related phenotypes in 121 laboratory‐housed chimpanzees. We used expert‐derived weights to obtain autism scores from ratings on the 43‐item Chimpanzee Personality Questionnaire; higher scores indicated more autistic‐like traits. The first model included fixed effects for sex, ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 84 publications
(112 reference statements)
0
2
0
Order By: Relevance
“…Nonhuman animals are important models for studies on the genomic and neural systems that contribute to behaviors that are used as model phenotypes of ASD (Bauman & Schumann, 2018 ; Silverman et al, 2022 ). In nearly all primate species used as animal models for ASD, different dimensions of social behavior or personality have been the behavioral phenotypes of interest (Yirmiya et al, 2006 ; Mahovetz, Young & Hopkins, 2016 ; Proctor, Calcutt, Burke & de Waal, 2016 ; Wilson et al, 2017 ; Parker et al, 2018 ; Weiss, Wilson & Hopkins, 2021 ; Gunter et al, 2022 ). By contrast, however, there are surprisingly few studies that have focused on overt measures of social cognition, including joint attention (Hopkins et al, 2014a).…”
Section: Joint Attention and Personality In Nonhuman Primatesmentioning
confidence: 99%
“…Nonhuman animals are important models for studies on the genomic and neural systems that contribute to behaviors that are used as model phenotypes of ASD (Bauman & Schumann, 2018 ; Silverman et al, 2022 ). In nearly all primate species used as animal models for ASD, different dimensions of social behavior or personality have been the behavioral phenotypes of interest (Yirmiya et al, 2006 ; Mahovetz, Young & Hopkins, 2016 ; Proctor, Calcutt, Burke & de Waal, 2016 ; Wilson et al, 2017 ; Parker et al, 2018 ; Weiss, Wilson & Hopkins, 2021 ; Gunter et al, 2022 ). By contrast, however, there are surprisingly few studies that have focused on overt measures of social cognition, including joint attention (Hopkins et al, 2014a).…”
Section: Joint Attention and Personality In Nonhuman Primatesmentioning
confidence: 99%
“…Polymorphisms in AVPR1A are also associated with a composite score reflecting ASD phenotypes (Weiss et al 2021) as well as social cognition measures linked to ASD, notably receptive joint attention (RJA) . Previous studies have also found that both humans and chimpanzees with poor joint attention skills differ in gray matter volume of the posterior, but not anterior, portion of the superior temporal gyrus (Hopkins, Misiura, et al 2014;Mundy 2018).…”
mentioning
confidence: 99%